ANALYSIS OF THE INFLUENCE OF SURPRISE ON THE EFFICIENCY OF THE TASKS OF NATIONAL GUARD OF UKRAINE UNITS IN A SPECIAL OPERATION TO NEUTRALIZE ILLEGAL ARMED GROUPS - Kolyanda, V. V.; Drobakha G. А. (Honor and Law, 2019)
We consider the importance of surprise as a factor for success in planning the operation (combat), the degree of achievement of surprise in terms of the internal armed conflict, as well as the influence of the factors of surprise on the efficiency of the tasks forces of Ukraine of the National Guard in a special operation to neutralize illegal armed formations.